Comparative Study of Financing Channels for Small and Medium-Sized Enterprises - Wang, Zhiming (Transactions on Economics, Business and Management Research, 2024)
Small and medium-sized enterprises (SMEs) are key to economic growth and job creation. However, they face significant challenges in accessing funding, which is essential for their growth and sustainable development. This paper analyzes several financing methods that can be adopted by SMEs in China, including bank loan, venture capital, angel investment, crowd funding, government grants, equity financing etc. The report evaluates the advantages and disadvantages of each pathway, focusing on accessibility, cost, approval process, etc. On this basis, combined with the actual situation of listed companies in China, the analysis of different types of financing models, to provide theoretical basis for the development of SMEs in China. In addition, the report also explores the financing of SMEs in the future, highlighting the use of technology, changes in government policies, and international collaboration that can improve SMEs’ financing capacity. Understanding this new development trend is that SMEs should adopt flexible financing strategies according to changes in the market environment, so as to ensure their sustainable development and make a greater contribution to the world economy. These results will provide theoretical basis for the rapid development of Chinese SMEs in the financing environment, as well as the formulation of related policies and the decision-making of investors.